2021
DOI: 10.1021/acs.jnatprod.0c01370
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Peptaibol Biosynthetic Promiscuity for Next-Generation Antiplasmodial Therapeutics

Abstract: Malaria remains a worldwide threat, afflicting over 200 million people each year. The emergence of drug resistance against existing therapeutics threatens to destabilize global efforts aimed at controlling Plasmodium spp. parasites, which is expected to leave vast portions of humanity unprotected against the disease. To address this need, systematic testing of a fungal natural product extract library assembled through the University of Oklahoma Citizen Science Soil Collection Program has generated an initial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…The 13 C NMR (Table ) and DEPT spectra displayed 79 carbon resonances, including 18 amide carbonyls, 16 α-amino carbons (seven methines, two methylenes, and seven nonprotonated), and 16 methyl carbons. These spectroscopic features suggested that compound 1 belonged to the family of peptaibol natural products containing 16–18 amino acid residues. …”
Section: Resultsmentioning
confidence: 98%
“…The 13 C NMR (Table ) and DEPT spectra displayed 79 carbon resonances, including 18 amide carbonyls, 16 α-amino carbons (seven methines, two methylenes, and seven nonprotonated), and 16 methyl carbons. These spectroscopic features suggested that compound 1 belonged to the family of peptaibol natural products containing 16–18 amino acid residues. …”
Section: Resultsmentioning
confidence: 98%
“…Combined analyses of 1 H-1 H COSY, HMBC, HSQC and TOCSY spectra further revealed the presence of 2 × Val, 2 × Leu, 2 × Pro, 2 × Aib, 1 × Asn, 1 × Ileol and N-Ac-Aib residues (Table 1), which were in accordance with the result of Marfey's analysis (Figure 3). The acetyl group was also assumed to be in one terminal as the cases found in known peptaibols, the HMBC of CO (δ C 170.8, Ac-)/NH-1 (δ H 8.59 s, Aib 1 ) indicated the first Aib 1 residue; subsequent ROESY correlations of NH-1/NH-2 (δ H 8.36 d, Asn 2 ), NH-2/NH-3 (δ H 7.70 d, Val 3 ), NH-3/NH-4 (δ H 7.34 d, Val 4 ), NH-4/NH-5(δ H 7.91 s, Aib 5 ), NH-5/δ-H 2 (δ H 3.64 -3.68 m, 3.39 dt, Pro 6 -δ-H 2 ), α-H (δ H 4.20 t, Pro 6 -α-H)/NH-7 (δ H 7.53 d, Leu 7 ), NH-7/ NH-8 (δ H 7.19 d, Leu 8 ), NH-8/NH-9(δ H 7.52 s, Aib 9 ), NH-9/δ-H 2 (δ H 3.62 -3.64 m, Pro 10 -δ-H 2 ) and α-H (δ H 4.22 -4.28 m, Pro 10 -α-H)/NH-11 (δ H 7.02 d, Ileol 11 ), established the planar structure of 6 as Ac-Aib 1 -Asn 2 -Val 3 -Val 4 -Aib 5 -Pro 6 -Leu 7 -Leu 8 -Aib 9 -Pro 10 -Ileol 11 , which was further confirmed by the MALDI-MS/MS analysis (Fig- ure 2) of 6.…”
Section: Resultsmentioning
confidence: 99%
“…Peptaibols are a family of linear peptides generally composed of 5-22 amino acid residues, characterized by N-acyl terminus, C-amino alcohol terminus, and a high proportion of nonproteinogenic amino acids such as αaminoisobutyric acid (Aib) or isovaline (Iva). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] In the past five years, peptaibols have attracted attentions of many natural product researchers for their potential bioactivities including cytotoxicities, [1][2][3][4][6][7][8][9]11,15,16] antibacterial activities, [1,2,11,13] antifungal activities, [9,10,12] anti-plasmodial activities [5] and anti-viral activities, [14] et al Peptaibols have been isolated from several genera of fungus, such as Trichoderma, [2][3][4][8][9][10][12][13][14]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peptaibols, the largest group of peptaibiotics, are a class of linear peptides that have an acylated N terminus group, a C-terminal amino acid, and a high content of α-aminoisobutyric acid (Aib)—approximately 40% of Aib in long peptaibols and from 14 to 56% in short peptaibols [ 7 , 11 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Peptaibols are dominant secondary metabolites of filamentous fungi including the ones exhibiting a mycoparasitic lifestyle [ 22 , 24 , 25 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%